2013
DOI: 10.1021/ie401087f
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Epoxidation of Propene with Hydrogen Peroxide Vapor

Abstract: A study on the gas-phase epoxidation of propene with vapor hydrogen peroxide has been carried out. The main purpose was to understand the key factors in the reaction and the relationship between epoxidation of propene and decomposition of hydrogen peroxide, which is the main side reaction. The decomposition was highly influenced by the materials used, being higher in metals than in polytetrafluoroethylene (PTFE) and glass, and it was complete when the epoxidation catalyst, TS-1, was introduced in the system. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
1
18
3
Order By: Relevance
“…Thus, constant TOF over different loadings of catalysts implies that the consumption of H 2 O 2 over the bed is small enough to be in a differential regime. This result is in contrast with the work of Ferrandez and co-workers where they observed constant conversion above 10 mg of catalyst, which can be attributed to the limited amount of H 2 O 2 in the system[22].…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, constant TOF over different loadings of catalysts implies that the consumption of H 2 O 2 over the bed is small enough to be in a differential regime. This result is in contrast with the work of Ferrandez and co-workers where they observed constant conversion above 10 mg of catalyst, which can be attributed to the limited amount of H 2 O 2 in the system[22].…”
contrasting
confidence: 99%
“…Ferrandez and co-workers tested propylene epoxidation with H 2 O 2 vapor over TS-1 and measured epoxidation rates of 10.5 kg po •kg cat -1 •h -1 with selectivity up to 90 % at an overall propylene conversion of 40% [22]. Although interesting studies, the authors provided neither kinetics results nor mechanistic insight into the gas-phase epoxidation because: 1) the experiments were stoichiometrically limited by hydrogen peroxide and consequently 2) the experiments were performed outside of differential conversion conditions.…”
mentioning
confidence: 99%
“…The formation of coproducts is especially problematic because their price and volume demand may not match those of propylene oxide, making optimization of the process difficult. Alternatives under consideration utilize hydrogen peroxide or H 2 plus O 2 (13)(14)(15) ). The H 2 O 2 route was pioneered by Enichem (16) with the discovery of a novel Ti containing zeolite TS-1, and in 2008 Evonik (former Degussa) and SKC first commercialized this technology (17).…”
Section: Introductionmentioning
confidence: 99%
“…The G‐HPPO reaction needs to be operated above 100°C in order to vaporize H 2 O 2 and H 2 O. H 2 O 2 , however, decomposes to H 2 O and O 2 at such a high temperature. According to literature, 5 increase the reaction temperature from 50°C (corresponding to the known liquid‐phase HPPO reaction) to 140°C (corresponding to G‐HPPO reaction) leads to the increase of H 2 O 2 decomposition rate constant 230 times, while only 9 times increase of epoxidation rate constant. Therefore, how to inhibit the decomposition of H 2 O 2 at high‐temperature is a major challenge for the development of a G‐HPPO process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, how to inhibit the decomposition of H 2 O 2 at high‐temperature is a major challenge for the development of a G‐HPPO process. In 2013, Perez et al studied the influence of reactor material on the decomposition of H 2 O 2 in G‐HPPO reaction, 5 and indicated that at high reaction temperature even the decomposition of H 2 O 2 on the surface of reactor can be a serious problem. Fortunately, the use of non‐metallic materials like polytetrafluoroethylene for G‐HPPO reactor is beneficial.…”
Section: Introductionmentioning
confidence: 99%